Towards modelling beef cattle management with Genetic Programming - Abbona, Francesca (2022)
Abbona, F., Vanneschi, L., Bona, M., & Giacobini, M. (2020). Towards modelling beef cattle management with Genetic Programming. Livestock Science, 241, 1-12. [104205]. https://doi.org/10.1016/j.livsci.2020.104205